Preserving Mangrove Forests as an Effort to Manage Disaster Risk in the Coastal Area of Pangandaran Regency - Nuranisa, Nisa; Mulyanie, Erni (Fakultas Pertanian Universitas Samudra, 2024)
Preserving mangrove forests as a disaster risk management strategy in the coastal areas of Pangandaran Regency is related to Indonesia's geographic vulnerability to natural disasters which causes Pangandaran Regency to become one of the areas with high disaster risk, especially in coastal areas. This study emphasizes the importance of community involvement in disaster management through planting and preserving mangroves which function as a natural barrier against coastal erosion, tsunamis and other disasters. The method used is descriptive through literature studies and documentation studies to analyze the existing mangrove ecosystem and its role in reducing disaster risk. The results of this article study contain various mangrove conservation initiatives and their ecological benefits, such as stabilizing coastlines and increasing community resilience to disasters and preserving mangrove forests as a disaster management effort in the coastal areas of Pangandaran Regency. This article aims to provide information to the government and local communities about sustainable mangrove conservation and preservation efforts as a buffer for coastal areas in facing disaster risks.